Effects of Pressure Gradients on Energy Dissipation Coefficient - Soleimani, Soheil; Ghasemi, E.; Almas, M.A. (Journal of Advanced Thermal Science Research, 2015)
In this study energy dissipation coefficient and entropy generation process in characteristic wall shear flows have been investigated. Effect of pressure gradients on energy dissipation coefficient for flows undergoing “bypass” transition from laminar to turbulent state has been studied. Reynolds-Averaged Navier-Stokes (RANS) models and Direct Numerical Simulations (DNS) are implemented to study the energy dissipation coefficient and local entropy generation in pre-transitional and transitional regions. Three of these RANS models are transitional models such as, traditional SST k-w (2eq), SST k-w (4eq) and k - kl -w and the results are compared with DNS. Four simulations have been performed for (1) zero, (2) favorable, (3) adverse and (4) strong-adverse pressure gradient cases. The numerical results show that the pressure gradient has a significant effect on energy dissipation coefficient and entropy generation.